A reactor model with delay because of convection - Švitra, Donatas; Bučys, Kostas (Lietuvos matematikos rinkinys, 2010)
In this article a model of a nuclear reactor which is made of two differential equations with delay was analysed. There was made a linear analysis and defined the area of the asymptotic stability of the model and the area in which there appears a stable periodical solution of one frequency. The analytic form of the mentioned solution was received using the bifurcation theory.
Keywords: nuclear reactor; differential equation; delay; stable solution; periodic solution; model; root